2017
DOI: 10.5897/ajar2017.12167
|View full text |Cite
|
Sign up to set email alerts
|

Biological nitrogen fixation by pigeon pea and cowpea in the doubled-up and other cropping systems on the Luvisols of Central Malawi

Abstract: Legumes form a very important component in Malawi's cropping systems because of their roles in food security, income generation and soil fertility improvement through biological nitrogen fixation (BNF). They are commonly grown in various cropping systems including sole cropping, cereal-legume intercrops and legume-legume intercrops (also commonly referred to as "doubled-up"). However, information on BNF by the pigeon pea and cowpea under doubled-up system is scanty. Therefore, a study was conducted at two site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The positive influence on the decision to grow legumes is supported by the long-standing view that legumes, including groundnuts, are 'women crops' (Nakazi et al, 2017;Orr, Kambombo, Roth, Harris, & Doyle, 2015). Although our results support this, other findings in the region show that for the main legume grown in the area, groundnuts, households headed by women tend to allocate less land to it and are 20% less productive (Joe-Nkamuke et al, 2019) than their maleheaded counterparts.…”
Section: Women Empowerment Shaping Uptake Of Legume and Manuresupporting
confidence: 54%
See 2 more Smart Citations
“…The positive influence on the decision to grow legumes is supported by the long-standing view that legumes, including groundnuts, are 'women crops' (Nakazi et al, 2017;Orr, Kambombo, Roth, Harris, & Doyle, 2015). Although our results support this, other findings in the region show that for the main legume grown in the area, groundnuts, households headed by women tend to allocate less land to it and are 20% less productive (Joe-Nkamuke et al, 2019) than their maleheaded counterparts.…”
Section: Women Empowerment Shaping Uptake Of Legume and Manuresupporting
confidence: 54%
“…When they enter the market and become profitable, they shift status from being subsistence to commercial. Then, men's participation increases but largely relies on women's knowledge for efficient management (Nakazi et al, 2017). However, the inclusion of women's role using WEAI even in male-headed households and its influence on both, the probability to grow legumes and their productivity, requires further scrutiny.…”
Section: Women Empowerment Shaping Uptake Of Legume and Manurementioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that there was a significant difference (P<0.01) in total number of nodules per plant at each WAP (table 6). Njira et al (2017) reported that number of nodules in pigeon pea was reduced when intercropped with cowpea. Further, Njira et al (2017) noted that, this may be due to the competition for resources when intercropping legume -legume or legume -cereals.…”
Section: Number Of Total Nodules Per Plantmentioning
confidence: 99%
“…Njira et al (2017) reported that number of nodules in pigeon pea was reduced when intercropped with cowpea. Further, Njira et al (2017) noted that, this may be due to the competition for resources when intercropping legume -legume or legume -cereals. Number of nodules increased with increasing row spacing [Banik et al, 2006].…”
Section: Number Of Total Nodules Per Plantmentioning
confidence: 99%